Discovery and optimization of new oxadiazole substituted thiazole RORγt inverse agonists through a bioisosteric amide replacement approach. Issue 12 (15th June 2020) - Steeneck, Christoph; Gege, Christian; Kinzel, Olaf; Albers, Michael; Kleymann, Gerald; Schlüter, Thomas; Schulz, Andreas; Xue, Xiaohua; Cummings, Maxwell D.; Fourie, Anne M.; Leonard, Kristi A.; Scott, Brian; et al.
Graphical abstract: Abstract: Starting from previously identified thiazole-2-carboxamides exemplified by compound 1/6, two new series of RORγt inverse agonists with significantly improved aqueous solubility, ADME parameters and oral PK properties were discovered. These scaffolds were identified from a bioisosteric amide replacement approach. Amongst the variety of heterocycles explored, a 1, 3, 4-oxadiazole led to compounds with the best overall profile for SAR development and in vivo exploration. In an ex vivo mouse PD model, concentration dependent efficacy was demonstrated and compounds 3/5 and 6/3 were profiled in a 5-day rat tolerability study.